2012
DOI: 10.1152/japplphysiol.01434.2011
|View full text |Cite
|
Sign up to set email alerts
|

Leg intramuscular pressures and in vivo knee forces during lower body positive and negative pressure treadmill exercise

Abstract: Quantifying muscle and joint forces over a broad range of weight bearing loads during exercise may provide data required to improve prosthetic materials and better protect against muscle and bone loss. Collectively, leg intramuscular pressure (IMP), ground reaction force (GRF), and the instrumented tibial tray force measurements provide a comprehensive assessment of leg muscle and joint biomechanical effects of gravity during exercise. Titration of body weight (BW) by lower body negative pressure (LBNP) and lo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
15
0

Year Published

2012
2012
2024
2024

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 16 publications
(16 citation statements)
references
References 29 publications
1
15
0
Order By: Relevance
“…LBPPS also raises the intramuscular pressure, which activates the muscle mechanoreflex, resulting in increased BP [17]. Furthermore, positive pressure on the lower extremities limits the blood supply to the active muscles, and hence metabolites accumulate and a pressure metaboreflex is triggered [1819]. …”
Section: Discussionmentioning
confidence: 99%
“…LBPPS also raises the intramuscular pressure, which activates the muscle mechanoreflex, resulting in increased BP [17]. Furthermore, positive pressure on the lower extremities limits the blood supply to the active muscles, and hence metabolites accumulate and a pressure metaboreflex is triggered [1819]. …”
Section: Discussionmentioning
confidence: 99%
“…Patil et al 3 found that the peak tibial force at 25% BW relative to peak tibial force at 100% BW was 1.9 BW/5.1 BW, corresponding to 37% at 25% BW. Macias et al 19 found an uneven load distribution between the instrumented leg and the healthy leg at high relative BWs and "high" velocity, tending toward more load on the healthy leg. This means that, in healthy subjects, with an even load distribution between left and right leg, we may expect values lower than 37%, as found by Patil et al 3 Macias et al 19 found values of approximately 30% at 20% BW (based on readings from their Figure 6).…”
Section: Discussionmentioning
confidence: 99%
“…Macias et al 19 found an uneven load distribution between the instrumented leg and the healthy leg at high relative BWs and "high" velocity, tending toward more load on the healthy leg. This means that, in healthy subjects, with an even load distribution between left and right leg, we may expect values lower than 37%, as found by Patil et al 3 Macias et al 19 found values of approximately 30% at 20% BW (based on readings from their Figure 6). Again, this value could be a bit overestimated due to the uneven weight distribution between the implanted knee and the healthy knee.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…It has been known since the first attempts to characterise the mechanical properties of skeletal muscles (Hill, 1948) that they generate significant IaMP during active contraction. Furthermore, IaMP was reported to correlate linearly with contraction force in skeletal muscles of humans, cats and rabbits (Baskin and Paolini, 1967;Sadamoto et al, 1983;Parker et al, 1984;Petrofsky and Hendershot, 1984;Sejersted et al, 1984;Aratow et al, 1993;Nakhostine et al, 1993;Davis et al, 2003;Ward et al, 2007;Winters et al, 2009;Macias et al, 2012). According to present knowledge, muscle contraction causes a reversible distortion of muscle architecture accompanied by an increase of IaMP, owing to muscle incompressibility (Swammerdam, 1737;Hill, 1948;Jenkyn et al, 2002).…”
Section: Introductionmentioning
confidence: 98%